Cattle producers' participation in market channels in Central America: supermarkets, processors, and auctions. - Balsevich, F.; Schuetz, P.; Pérez, E. (Michigan State University, 2006)
This paper focuses on the determinants and effects of the participation of cattle producers in the supermarket channel, export processor channel, and traditional auction channel. It begins with the analysis of the market channels using qualitative data from 50 interviews of retailers, processors, auction market managers, and other key informants in Costa Rica and Nicaragua, two widely differing cases. It then analyzes patterns and supplies of producers by channel using farm level data (from the authors’ survey of farmers in 2004) from 300 farms in the two countries.